The Influence of Learning Agility, Change Readiness, and Digital Competence on Employee Digital Readiness in the Financial and Banking Industry - Fauzie Senoaji; Tri Susilowati; Mohammad Azharie Hamdany; Riesna Apramilda; Niken Widyastuti; Tyahya Whisnu Hendratni (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the influence of learning agility, change readiness, and digital competence on employee digital readiness in the financial and banking industry. This study used a quantitative approach with a survey method of 150 respondents working in financial and banking institutions in Indonesia. The sampling technique used purposive sampling with the criteria of respondents who have worked for at least one year, actively use digital technology in their work, and have participated in digital training. Data analysis was conducted using multiple linear regression to test the simultaneous and partial effects between variables. The results showed that all three independent variables have a positive and significant effect on employee digital readiness. Partially, learning agility improves digital adaptability, change readiness strengthens psychological readiness for transformation, and digital competence improves employees' technical skills. Theoretically, this study expands the study of digital human resource management, while practically, it provides guidance for financial and banking companies to develop training strategies and policies that support the digital readiness of the workforce in the era of technological transformation.